Increasing Fee Based Income (FBI) Through Optimizing BNI Mobile Banking Features to Support Banking Performance - Nyoman Wendy Saputra; Luh Putu Mahyuni (Quantitative Economics and Management Studies, 2024)
The significance of conducting this research is related to the performance of BNI Mobile Banking which is far behind its competitors which will have an impact on the performance of PT. Bank Negara Indonesia (Persero) Tbk. The aim of the research is to determine the factors that are important to customers regarding the BNI Mobile Banking application and the level of satisfaction with these important factors. This research uses a quantitative approach to BNI customers on the island of Bali with a total of 204 respondents randomly using the Slovin formula and representing each regency of Bali Province. The data was analyzed using the Importance Performance Analysis (IPA) method with the outcomes 12 indicators which according to respondents were important but received an adequate to insufficient level of satisfaction to be an improvement for the company, including: 1) The BNI Mobile Banking application can be downloaded on all cellular operating systems (Android and Apple Store); 2) The BNI Mobile Banking application can be used anywhere (domestic and overseas) as long as there is a cellular signal; 3) BNI Mobile Banking can fulfill all online customer banking needs; 4) BNI Mobile Banking provides information and products that suit customer preferences; 5) BNI Mobile Banking provides services according to the promised time; 6) BNI Mobile Banking has more than one security code to minimize transactions that are not carried out by the customer; 7) BNI Mobile Banking provides a service menu that helps users if problems occur; 8) BNI Mobile Banking immediately responds to problems faced by customers; 9) BNI Mobile Banking will refund funds if the transaction was not carried out by the customer; 10) BNI Mobile Banking will refund funds if the transaction via mobile banking fails; 11) Easy to contact BNI Mobile Banking services; and 12) Call center services can provide satisfactory responses to problems faced by customers.